Formulation and Effectiveness Test of Matoa Stem (Pometia Pinnata) Skin Extract Cream Combination of Honey on Staphylacoccus Aureus Bacteria (Medico Legal Update, 2020)
Matoa (Pometia Pinnata) is a typical Papua fruit plant, classified as a large tree with an average height of18 meters with a maximum average diameter of 100 cm. Generally bear fruit once a year, flowering inJuly to October and fruiting 3 or 4 months later. Some research shows that the leaves, fruit bark and matoatree bark contain tannins, saponins and alkaloids. The purpose of this study was to produce a formulationand test the effectiveness of a cream extract of matoa tree bark (pometia pinnata) honey combination onstaphylacoccus aureus bacteria. This research is a purely experimental research to produce an extract ofthe matoa tree bark cream and then test its effectiveness in the treatment of staphylococcus aureus bacteria,with a completely randomized design (CRD) design. The results showed that the matoa rind extract creamwas effective against staphylacoccus aureus bacteria with a significant value of 0.00